2022
DOI: 10.1371/journal.pone.0269944
|View full text |Cite
|
Sign up to set email alerts
|

Beliefs, barriers and hesitancy towards the COVID-19 vaccine among Bangladeshi residents: Findings from a cross-sectional study

Abstract: Background COVID‐19 vaccination acceptance is important, and combating hesitancy which is generally based on the individuals’ beliefs and perceptions is essential in the present pandemic. This study assesses COVID‐19 vaccine hesitancy and associated factors, beliefs and barriers associated with COVID-19 vaccination. Methods A cross-sectional study was carried out among 492 Bangladeshi residents (76% male; mean age = 24.21 ± 4.91 years; age range = 18–50 years) prior to the nationwide mass COVID-19 vaccinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 65 publications
1
7
0
1
Order By: Relevance
“…Similar to findings in Bangladeshi [ 6 ], participants in this study showed that some individuals in Zimbabwe believed that mass vaccination would be the most effective approach to combating the COVID-19 pandemic; however, concerns regarding the side effects of the vaccine, vaccine effectiveness and safety delayed vaccine uptake by the population. Such concerns can lead to vaccine hesitancy.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Similar to findings in Bangladeshi [ 6 ], participants in this study showed that some individuals in Zimbabwe believed that mass vaccination would be the most effective approach to combating the COVID-19 pandemic; however, concerns regarding the side effects of the vaccine, vaccine effectiveness and safety delayed vaccine uptake by the population. Such concerns can lead to vaccine hesitancy.…”
Section: Discussionsupporting
confidence: 80%
“…Those with high concern about COVID-19 reported that they would take the COVID-19 vaccine [ 5 ]. In Bangladesh, 26.42% of respondents were hesitant about the COVID-19 vaccine, 70.33% were either already vaccinated or were willing to get vaccinated, and 3.25% refused it definitely [ 6 ]. In the United States, willingness to be vaccinated decreased with time due to concerns about the side effects and long-term health problems, as well as doubts about the vaccine’s efficiency [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several initiatives are being implemented in Afghanistan to prevent vaccination hesitancy, including routine immunization vaccinators and the deployment of 2,000 more new health professionals (teams of two people: one male and one female), raising societal awareness and educating them, and avoiding myths ( 35 ). Similarly, in Bangladesh, the most popular variables contributing to decreasing vaccination hesitancy include social media and awareness campaigns ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…A cross-sectional study conducted in Nigeria [ 53 ] and Egypt [ 54 ] showed that respectively, 50.5% and 42% of healthcare workers exhibited vaccine hesitancy. Vaccine hesitancy may have been related to healthcare providers’ fears of adverse effects in their future pregnancies and other medical complications, efficacy uncertainty, inadequate vaccine trials prior to human administration, doubts about vaccine benefits, misinformation and disinformation about the vaccine’s side effects [ 55 ].…”
Section: Discussionmentioning
confidence: 99%